Melacak asal-usul keris dan peranannya dalam sejarah nusantara - Mahyudin Al-Mudra, (Universiti Kebangsaan Malaysia, 2009)
This article is interested in highlighting the historical role of the keris rather than its physical manifestation. Although the keris is a weapon that can cause injury, all weapons are not keris as it is distinguished by the methods and material which has been used to create it. In the Malay civilaization, a keris is a special cultural artifact with a specific role. This article will focus on the rise of the keris and its role in Nusantara’s historical development, particularly in Jawa